ANALISIS KANDUNGAN POLIFENOL DAN UJI AKTIVITAS ANTIOKSIDAN DARI BUAH MARKISA (Passiflora edulis) - Aco Mappacanda (As-Syifaa Jurnal Farmasi, 2010)
This study aims to analyze and determine the levels of polyphenols content from passion fruit (Passiflora edulis) is particulary cultivated in the central region of Malino in South Sulawesi regencies of Gowa, and test the antioxidant activity compared with ascorbic acid (vitamin C) is also one of the body’s antioxidant. This research  was conducted by using UV-visible spektrophotometry and as reagents used Folin Ciocalteu solution and 15% Na2CO3 produces a blue color, read absorbtion at 670 nm wavelength. As a standard solution used with tannat acid concentration 0,5 ppm, 1,0 ppm, 2 ppm, 4 ppm and 8 ppm. To test the antioxidant activity is also using UV-visible spectrophomometry and used as reactant solution concentration of DPPH with 1 mM (milimolar), read absorbtion at 515 nm wavelength with color change from purple to yellow to dark brown. Used as a standard solution of ascorbic acid concentration 20 ppm, 40 ppm, 80 ppm and 160 ppm. The result showed that the 2 varieties of passion fruit (Passiflora edulis) contain levels of polyphenols with poliphenol content of the purple passion fruit (Passiflora edulis Sims var. Edulis) of 0.5768 mg/100 ml and the yellow passion fruit (Passiflora edulis L var. Flavicarpa Degener) 1.1278 mg/100 ml. To study the antioxidant activity of the test result is the percentage of resistance in purple  passion fruit (Passiflora edulis Sims var. Edulis)  of 90.65% and yellow passion fruit (Passiflora edulis  L var. Flavicarpa Degener) for 47.32%.Keyword : Polifenol, Passiflora edulis, Spectrofotometric UV-Vis